THE EFFECT OF CONSCIOUSNESS-RAISING TASK (CRT) ON STUDENTS’ GRAMMARCOMPETENCE - Mahfud Mahfud (Language-Edu, 2021)
This study aims to investigate the implementation of Consciousness Raising Task on learners’ grammar competence The aims of this research was to discover the effect of consciousness raising task of students’ grammar competence of basic level at Al-Fitrah English Course pare Kediri. This study utilized pre-experimental design also, this study was finished in six meetings. First meeting was pre-test, second until fifth meeting was treatment and the sixth meeting was post test. The data was collected by utilizing multiple choice of Grammar test. The data gained were analyzed by using paired sample t-test formula. After doing the pre-experimental research steps, the researcher got some data. The data gave information that there was significant difference on students’ grammar competence by using Consciousness Raising Task. It was discovered that the mean score of the pre-test was 57.40 and the mean score of the post-test was 73.80. From the data it can be concluded that there are differences of the results because mean score pretest 57.40 is lower than the mean score of post test 73.80. Therefore, it could be inferred that the application of Consciousness Raising Task is compelling.